Augmented reality technology in learning German as a foreign language: technological and didactic aspects - Svitlana M. Amelina; Rostyslav O. Tarasenko; Yuliya M. Kazhan (CTE Workshop Proceedings, 2024)
This paper explores the application of augmented reality (AR) technology for developing foreign language professional communication skills in learning German. The study involved creating a virtual tour of architectural landmarks in Kyiv related to German architects, with AR elements like QR codes linking to textual, visual and video information and 3D models. The technological and didactic requirements for implementing AR were determined. Students prepared informative materials and tested the tour. The results of the questionnaire confirmed the motivational effect and expanded content from AR. Some difficulties were the dependence on gadgets and software. AR elements facilitated remembering terminology in context. The approach allows combining speciality content and language learning. AR technology can potentially enhance the learning process, but further research on methods is needed.